Serum hepatitis B virus large and medium surface proteins as novel tools for predicting HBsAg clearance - Lin, Xiao; Zheng, Yanhong; Li, Hong; Lu, Junfeng; Ren, Shan; Liu, Yisi; Wang, Xiaoxiao; Zheng, Sujun; Ma, Lina; Cao, Zhenhuan; Chen, Xinyue (Frontiers in Immunology, 2022)
Background: There is still lack of reliable predictors for hepatitis B surface antigen (HBsAg) clearance. Recent studies have shown that the levels of large (LHBs) and medium hepatitis B surface proteins (MHBs) are closely related to antiviral efficacy. This study aimed to investigate the possibility of LHB and MHB levels to predict HBsAg clearance. Methods: An inactive HBsAg carriers (IHCs) cohort that had received pegylated interferon (Peg-IFN) treatment was divided into the HBsAg-cleared group (R group) and the HBsAg non-cleared group (NR group) based on whether HBsAg was cleared at 96 weeks. We detected the levels of LHBs and MHBs to evaluate the possibility of predicting HBsAg clearance. Results: There were 39 patients in the R group and 21 in the NR group. The total HBsAg, LHB, and MHB levels at baseline and at 12 weeks were significantly lower in the R group than in the NR group (all p < 0.05). Multivariate logistic regression indicated that LHB and MHB levels at baseline and 12 weeks were independent predictors of HBsAg clearance (OR = 0.435, p = 0.016; OR = 0.136, p = 0.003; OR = 0.137, p = 0.033; OR = 0.049, p = 0.043). The area under the curve (AUC) for the baseline and 12-week LHB and MHB levels was 0.827-0.896, which were greater than that of the total HBsAg level at baseline and 12-week (AUC: 0.654-0.755). Compared with the prediction results of a single indicator, the combination of LHB and MHB levels had better value in predicting HBsAg clearance. The AUCs of combination factor 1, constructed from baseline LHB and MHB, and combination factor 2, constructed from 12-week LHB and MHB, were 0.922 and 0.939, respectively, and the sensitivity (82.05%-100.00%) and specificity (85.71%-100.00%) were both high. The combined indicators based on baseline LHBs ≤ 13.99 ng/mL and MHBs ≤ 7.95 ng/mL predicted HBsAg clearance rate of more than 90%. Conclusion: Baseline and 12-week LHB and MHB levels can predict HBsAg clearance obtained by Peg-IFN therapy in IHCs, and the predictive value is higher than that of the total HBsAg levels.